Intertrochanteric fracture fixation with dynamic hip screw: is tip-apex distance measurement useful for predicting fixation failure? - Goh, Kian Liang; Zakaria@Mohamad, Zamzuri; Sharifudin, Mohd Ariff; Mohamed Amin, Mohamed Azril (Faculty of Medicine, International Islamic University Malaysia, 2016)
Introduction: Application of dynamic hip screw (DHS) implant for the treatment of unstable intertrochanteric fractures continues to raise concern related to risk of lag screw cut-out with or without subsequent damage to the acetabulum. Measurement of tip-apex distances (TAD) has been recommended to guide the optimal placement of lag screw and to predict subsequent risk of screw cut-out. In this study, the value of TAD was evaluated to verify its usefulness. Methods: This is a retrospective study of 33 consecutive patients with intertrochanteric fracture treated with DHS. Demographic data of the patients were traced from their case notes. Post-operative radiographs were reviewed by focusing on measurement of TAD on anteroposterior and lateral radiographs. Radiographs at one year follow-up were reviewed to depict any fixation-related failure or complication. Results: Fifty two percent of patients did not achieved the recommended TAD of ≤ 25mm. The mean post-operative TAD was 25.9mm and elderly patients were likely to achieve TAD of ≤ 25mm. The overall complication rate of 6% was attributed to screw cut-out in two cases. The unstable left-sided fracture was identified to be a potential risk for screw cut-out or migration. Conclusion: TAD is a valuab